The Effect of Green Accounting and Corporate Social Responsibility (CSR) Implementation on the Financial Performance of Coal Energy Subsector Companies Listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024 - Gregorius Teja Sukma; Heni Haryani; Yanti Sri Wahyuni; Dian Widiyati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the impact of implementing Green Accounting and disclosing Corporate Social Responsibility (CSR) on the financial performance of coal companies within the energy sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research is motivated by growing environmental awareness and regulatory pressures compelling companies—particularly those in environmentally sensitive industries—to integrate environmental and social aspects into their business practices. A quantitative research approach was employed, utilizing secondary data obtained from annual reports and sustainability reports published by the companies. The sample was selected using a purposive sampling method based on data availability and consistency throughout the observation period. Financial performance was measured using profitability indicators, while Green Accounting was proxied by environmental cost disclosures, and CSR was measured using a CSR disclosure index. Data were analyzed using multiple linear regression after satisfying classical assumption tests. The results indicate that the implementation of Green Accounting has no significant effect on financial performance, and CSR disclosure likewise shows no significant impact on financial performance. Simultaneously, Green Accounting and CSR do not significantly affect the financial performance of coal companies in the energy sub-sector. These findings suggest that environmental and social responsibility practices do not contribute to improved financial performance, even in industries with significant environmental impacts. This study provides empirical evidence for management, investors, and regulators regarding the importance of sustainability-oriented accounting and reporting practices.